AB1070 Adverse events with short vs long-term pegloticase therapy in trials of refractory chronic gout. (23rd January 2014) - Wolfson, M.; Rehrig, C.; Bahrt, K.
Abstract : Background: Pegloticase was approved for the treatment of refractory chronic gout in the U.S. in 2010. The pegloticase registration program comprised 2, 6-month placebo-controlled Phase 3 trials (RCTs) followed by an open-label (OL) safety study for a total treatment duration of up to 3 yrs. Pegloticase was tested at two dosing regimens; 8 mg q2weeks (approved) and 8 mg q4weeks and patients had the option of changing regimens during the OL extension study. Objectives: To evaluate short and long-term safety with the approved biweekly dose of pegloticase in patients who received this regimen for the full RCT and extension study period. Methods: A subgroup of patients was identified from the pegloticase Phase 3 clinical trials who did not switch pegloticase dosing regimen (n=143) for the full duration of their exposure. The pattern and timing of all treatment emergent adverse events was evaluated for these patients during the 2.5 yrs of treatment (long term treatment) and compared with the AE profile in the pooled RCTs (short-term treatment). Adverse events were analyzed descriptively (total number per patient per year), and by type, for these patients receiving pegloticase q2weeks and q4weeks. Results: The Table shows the number, total exposure and rates of all adverse events, along with clinically relevant classes of AEs, for patients receiving a consistent dosing regimen of biweekly or monthly pegloticase. Rates of AEs were not increased with long term vs. short term pegloticase exposure. As may have been expected, gout flares were less common with long term pegloticase use. Conclusions: This analysis of adverse events in patients receiving a consistent regimen of pegloticase shows that the rate of all adverse events was not increased with long term vs. short term therapy. Gout flares and infusion-related reactions were less common with the approved q2week dose vs. the q4week dose for both short-term and long-term treatment. No evidence of new safety concerns or increased adverse events was revealed in this analysis of long-term (up to 3 yrs) pegloticase use. Disclosure of Interest: M. Wolfson Shareholder of: Savient, Employee of: Savient, C. Rehrig Shareholder of: Savient, Employee of: Savient, K. Bahrt Shareholder of: Savient, Employee of: Savient